Synthesis and Application of Nanomagnetic Immobilized Phospholipase C - Yang Jiang; Jing Du; Honglin Tang; Xin Zhang; Wenbin Li; Liqi Wang; Lianzhou Jiang; Dianyu Yu (Journal of Chemistry)
The nanomagnetic carrier (Fe3O4@SiO2@p(GMA)) was prepared by atom transfer radical polymerization, and then, the free phospholipase C (PLC) was immobilized on it proved by the results of FT-IR analysis. The enzyme loading was 135.64 mg/g, the enzyme activity was 8560.7 U/g, the average particle size was 99.86 ± 0.80 nm, and the specific saturation magnetization was 16.00 ± 0.20 emu/g. PLC-Fe3O4@SiO2@p(GMA) showed the highest activities at the pH of 7.5, and tolerance temperature raised to 65°C in soybean lecithin emulsion. Enzymatic degumming with PLC-Fe3O4@SiO2@p(GMA) under the conditions of the enzyme dosage of 110 mg/kg, reaction temperature of 65°C, pH of 7.5, and reaction time of 2.5 h resulted in residual phosphorus of 64.7 mg/kg, 1,2-diacylglycerol (1,2-DAG) contents of 1.07%, and oil yield of 98.1%. Moreover, PLC-Fe3O4@SiO2@p(GMA) still possessed more than 80% of its initial activity after 5 cycles.